Clinical Research Informatics: Survey of Recent Advances and Trends in a Maturing Field - Embi, P. J. (Yearbook of Medical Informatics, 2013)
Objectives: To provide a survey of the field of clinical research informatics (CRI), focusing in particular on significant developments over the past 3 years and the insights they provide about the progress and state of the field.Methods: An iterative “scoping review” of the literature published in scientific journals and conference proceedings that are relevant to CRI, from late 2009 to early 2013.Results: 212 articles were identified, and 64 were selected to illustrate recent advances in the field. Based on those, six categories of CRI activity were identified: Data and Knowledge Management, Discovery and Standards; Clinical Data Re-Use for Research; Researcher Support and Resources; Participant Recruitment; Patients/Consumers and CRI; Policy, Regulatory and Fiscal Matters.Conclusions: This survey demonstrates that the field of CRI has matured and is now well established. The ongoing work is essential to overcome many of the challenges the clinical research enterprise is facing and more work is needed. Even as work continues to establish necessary infrastructure, methods, and best practices, CRI researchers should strive for more rigorous study designs to evaluate the impacts of the work in the field. There is little doubt that the field is poised for rapid growth, and that the CRI literature will continue to reflect that growth in years to come.
Keywords: Clinical research; medical informatics; clinical trials; translational science; review literature as topic